1980
DOI: 10.1007/bf01059385
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution kinetics of tetraethylammonium ion in the rat

Abstract: Tissue distribution kinetics of tetraethylammonium (TEA) ion in rats were studied following both constant-rate intravenous infusion and rapid intravenous injection of the drug. At a steady-state plasma concentration of 0.2 microgram/ml, the tissue-to-plasma (T/P) concentration ratio of the kidneys, liver, heart, gut, and lungs exceeded 1, indicating that TEA is localized in these tissues. In vitro tissue homogenate binding and slice uptake experiments provided no evidence of TEA binding to tissue constitutents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Interestingly, although there may be minor species differences, OCTN1 and OCTN2 are expressed in various tissues, while OCT1 and OCT2 are expressed in kidney, liver, and intestine. A previous study on the tissue distribution of TEA in rats demonstrated that TEA accumulated in several tissues, including heart, gut, lung, and skin as well as liver and kidney in rats . Since TEA is hydrophilic and does not readily cross the cell membrane without the participation of a specific transporter, these tissues presumably contain a TEA transporter.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, although there may be minor species differences, OCTN1 and OCTN2 are expressed in various tissues, while OCT1 and OCT2 are expressed in kidney, liver, and intestine. A previous study on the tissue distribution of TEA in rats demonstrated that TEA accumulated in several tissues, including heart, gut, lung, and skin as well as liver and kidney in rats . Since TEA is hydrophilic and does not readily cross the cell membrane without the participation of a specific transporter, these tissues presumably contain a TEA transporter.…”
Section: Discussionmentioning
confidence: 98%
“…The present study allowed a more physiologically relevant approach (Mintun et al 1980) which was based on direct observation of concentrations in the various tissues. Tissues with proportional specific activities over the 24-432 h observation period were considered to have similar kinetic behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Creatinine, being cleared mainly by glomerular filtration, provides direct information only on the capacity for glomerular filtration but in many circumstances may correlate poorly with the other func tions o f the nephron, namely, tubular secretion and reab sorption. Because o f this limitation, several compounds have been investigated for their ability to measure the secretory capacity o f the kidney; these include p-aminohippuric acid [2], phenolsulphonephthalein [3] and tetraethylammonium [4], However, these substances are all ex ogenous and therefore need to be infused. In addition, for organic anions such as p-aminohippurate, other anions that can accumulate in uraemic blood may inhibit the renal tubular secretion o f the marker [5].…”
Section: Introductionmentioning
confidence: 99%